Working women work-life conflict at Perbadanan Nasional Berhad (PNS), Bangsar South / Nurdini Solehah Amiruddin - Amiruddin, Nurdini Solehah (2016)
Work-life conflict is an element that may affect an individual wellbeing. The past research stated that women were suffered more in dealing with work-life conflict as to be compared with men. This paper aims to explore the factors that lead to working women work-life conflict at Perbadanan Nasional Berhad, Bangsar South. As for this research paper, four elements have been identified as to be the main factors that leads to this conflict which are household responsibilities, organizational culture, work overload and financial need. The study used purposive sampling techniques in determining the sample size where only 107 female employees were selected to be the respondents. The study reported that all of the variable which are household responsibilities, organizational culture, work overload and financial need were significant and had becoming the major factors that lead to work-life conflict among working women nowadays. This study will help an organization to better understand their female employees major conflict while setting a new strategy for this group in order to balancing between their work and personal life.